A CRITICAL STUDY OF CLINTON BENNETT’S THOUGHTS TOWARDS SIRAH OF THE HOLY PROPHET ﷺ - Hameed, Abdul; Faisal Qureshi, Hafiz Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
Sirah of the Holy Prophet ﷺ is the topic on which a lot of work has been done both in the Muslim and non-Muslim world. For Muslims it was the source of aspiration and adaptation for the practical purposes of social life while for the non-Muslims it was the source of inquisitiveness and understanding Islam as a successful religion in the past and present time. Therefore, Muslim enthusiastic interest in the biography of the Holy Prophet ﷺ developed and evolved into a regular science while the west has modified the knowledge of biography according to their own order of preference but within the same biographic precedents. Both have tried to reconstruct the biography of the Holy Prophet ﷺ historically, chronologically and logically. Clinton Bennett is one of the western scholars who has contributed not only in the Islamic literature but also the biographic field. His work consists of numerous issues in Islam. Whatever he has learned from Islam and the Sirah of Holy Prophet and thus concluded in the form of his own thoughts, he has expressed most of them in his famous five books for example ‘In Search of Muhammad’, ‘Muslims and Modernity’, ‘Studying Islam’, ‘Interpreting the Qur’an’, and ‘Victorian Images of Islam’ (doctoral thesis)’. This study focuses on Clinton Bennett’s work on Sirah specifically with his broader view of the subject. This research is descriptive and analytical in nature and presents a detailed analysis of the work it is based upon.